Antitumor polysaccharides from mushrooms: a review on the structural characteristics, antitumor mechanisms and immunomodulating activities. (7th April 2016) - Meng, Xin; Liang, Hebin; Luo, Lixin
Graphical abstract: Abstract: Mushrooms are popular folk medicines that have attracted considerable attention because of their efficient antitumor activities. This review covers existing research achievements on the mechanisms of isolated mushroom polysaccharides, particularly (1→3)-β-D-glucans. Our review also describes the function in modulating the immune system and potential tumor-inhibitory effects of polysaccharides. The antitumor mechanisms of mushroom polysaccharides are mediated by stimulated T cells or other immune cells. These polysaccharides are able to trigger various cellular responses, such as the expression of cytokines and nitric oxide. Most polysaccharides could bind other conjugate molecules, such as polypeptides and proteins, whose conjugation always possess strong antitumor activities. The purpose of this review is to summarize available information, and to reflect the present situation of polysaccharide research filed with a view for future direction.